Elastomeric composites based on carbon nanomaterials - Araby, Sherif; Meng, Qingshi; Zhang, Liqun; Zaman, Izzuddin; Majewski, Peter; Ma, Jun (IOP Publishing, 2015)
Carbon nanomaterials including carbon black (CB), carbon nanotubes (CNTs) and graphene have attracted increasingly more interest in academia due to their fascinating properties. These nanomaterials can signiﬁcantly improve the mechanical, electrical, thermal, barrier, and ﬂame retardant properties of elastomers. The improvements are dependent on the molecular nature of the matrix, the intrinsic property, geometry and dispersion of the ﬁllers, and the interface between the matrix and the ﬁllers. In this article, we brieﬂy described the fabrication processes of elastomer composites, illuminated the importance of keeping ﬁllers at nanoscale in matrices, and critically reviewed the recent development of the elastomeric composites by incorporating CB, CNTs, and graphene and its derivatives. Attention has been paid to the mechanical properties and electrical and thermal conductivity. Challenges and further research are discussed at the end of the article.